A conceptual framework for computational models of Achilles tendon homeostasis. (11th June 2013) - Smith, David W.; Rubenson, Jonas; Lloyd, David; Zheng, Minghao; Fernandez, Justin; Besier, Thor; Xu, Jiake; Gardiner, Bruce S.
Abstract : Computational modeling of tendon lags the development of computational models for other tissues. A major bottleneck in the development of realistic computational models for Achilles tendon is the absence of detailed conceptual and theoretical models as to how the tissue actually functions. Without the conceptual models to provide a theoretical framework to guide the development and integration of multiscale computational models, modeling of the Achilles tendon to date has tended to be piecemeal and focused on specific mechanical or biochemical issues. In this paper, we present a new conceptual model of Achilles tendon tissue homeostasis, and discuss this model in terms of existing computational models of tendon. This approach has the benefits of structuring the research on relevant computational modeling to date, while allowing us to identify new computational models requiring development. The critically important functional issue for tendon is that it is continually damaged during use and so has to be repaired. From this follows the centrally important issue of homeostasis of the load carrying collagen fibrils within the collagen fibers of the Achilles tendon. Collagen fibrils may be damaged mechanically—by loading, or damaged biochemically—by proteases. Upon reviewing existing computational models within this conceptual framework of the Achilles tendon structure and function, we demonstrate that a great deal of theoretical and experimental research remains to be done before there are reliably predictive multiscale computational model of Achilles tendon in health and disease. WIREs Syst Biol Med 2013, 5:523–538. doi: 10.1002/wsbm.1229 This article is categorized under: Models of Systems Properties and Processes > Organ, Tissue, and Physiological Models